ANTIHYPERGLYCEMIC AND HYPOLIPIDEMIC EFFECTS OF METHANOLIC EXTRACT OF EUPHORBIA PROSTRATA ON ALLOXAN INDUCED INDUCED DIABETIC RABBITS - Shamim, Tahira; Ahmad, Mahmood; Mukhtar, Muhammad (European Scientific Journal, ESJ, 2014)
In past numerous medicinal plants had been used for the control of diabetes because of their antihyperglycemic effect but there was no scientific proof of it. Aim of current study was to evaluate antihyperglycemic and hypolipidemic effect of whole plant of Euphorbia prostrata (Family: Euphorbiaceae) in order to validate its traditional use in diabetes, by native people of Cholistan desert, Pakistan. Whole plant (methanolic extract) of Euphorbia prostrata (EP) (250 and 500 mg/Kg/day, per oral for 14 days) was evaluated in alloxan induced diabetic rabbits (150 mg/Kg., i/p.) by serum biochemical parameters. Glibenclamide (5 mg/Kg/day, p.o. for 14 days) was used as standard antidiabetic drug. Alloxan induced diabetic groups had elevated levels of fasting blood glucose, cholesterol and triglyceride levels when compared with control group. EP extract (both doses of 250 and 500 mg/Kg) exhibited antidiabetic effect by significant reduction of fasting blood glucose levels. 500 mg/Kg dose of EP produced more significant (P< 0.05) results as compared to 250 mg/Kg dose. Serum cholesterol and triglyceride levels were also lowered doen at the end of study. Therefore, outcome of the present study validate the traditional claims on antihyperglycemic effects of Euphorbia prostrata (whole plant).